1987
DOI: 10.1159/000298771
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic Receptors in Inner and Outer Layers of Human Myometrium Near Term: Characterization of Beta-Adrenergic Receptor Sites by [<sup>125</sup>I]-Iodocyanopindolol Binding

Abstract: The Β-adrenergic receptors present in inner and outer layers of human myometrium near term were characterized using the radioiodinated antagonist iodocyanopindolol (ICYP). In both layers ICYP binding is saturable, rapidly reversible, stereoselective, and appears to occur in a single class of sites with a KD of 30 pmol/l. Adrenergic agonists compete for ICYP binding sites with an order of potency consistent with Β2-adrenergic potencies: isoproterenol > epinephrine > > norepinephrine. Studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
1
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 10 publications
(13 reference statements)
4
24
1
1
Order By: Relevance
“…Consistent with our previous report where b-AR binding properties were described in human pregnant myometrium (Breuiller et al, 1987), the high-affinity binding site found here resembled that of a b 2 -AR profile. The identity of the low-affinity binding site was confirmed by competition-binding experiments.…”
Section: Rouget Et Al Human Myometrial B-adrenoceptors Desensitisasupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with our previous report where b-AR binding properties were described in human pregnant myometrium (Breuiller et al, 1987), the high-affinity binding site found here resembled that of a b 2 -AR profile. The identity of the low-affinity binding site was confirmed by competition-binding experiments.…”
Section: Rouget Et Al Human Myometrial B-adrenoceptors Desensitisasupporting
confidence: 93%
“…Our results provide strong evidences for resistance of b 3 -AR to the agonist-induced desensitisation in human near-term myometrium. Nevertheless, our binding experiments show that b 3 -AR are more numerous than b 2 -AR in near-term myometrium, while it was admitted that the predominant subtype was the b 2 -AR subtype in this tissue (Hayashida et al, 1982;Breuiller et al, 1987). b 3 -AR have not been previously detected, probably because of insensitive experimental conditions such as unadapted (i.e.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In addition, the myometrial ␤ 3 -adrenoceptor seems to be resistant to agonist-induced desensitization (Rouget et al, 2004). By contrast, ␤ 2 -adrenoceptor expression is either decreased (Breuiller et al, 1987;Chanrachakul et al, 2003) or unchanged (Gsell et al, 2000) at the end of pregnancy, and there is a loss of response to ␤ 2 -mimetics after chronic exposure to these drugs (Berg et al, 1983). This might partly explain the lack of efficacy of ␤ 2 -mimetics at the end of pregnancy.…”
Section: Abbreviations: Sar150640 Ethyl-4-{trans-4-[((2smentioning
confidence: 99%
“…Myometrial samples, collected on ice, were dissected free of endometrium and serosa and quickly frozen at -8 0°C . The effectiveness of these procedures, currently performed for other stud ies, were proved by microscopic investigations as pre viously reported [13].…”
Section: Biological Samplesmentioning
confidence: 94%